The importance of mathematical disposition and procedural-conceptual knowledge for elementary school teachers - Imam Kusmaryono; Hevy Risqi Maharani; Kartinah Kartinah (Universitas PGRI Madiun, 2022)
The success of learning mathematics in elementary schools is strongly influenced by the level of mathematical disposition, procedural knowledge, and conceptual knowledge of a teacher. This study follows an explanatory sequential design with the objectives of (1) investigating the effect of mathematical disposition on elementary school teachers' mathematical knowledge; and (2) describing the relationship between mathematical disposition, procedural knowledge, and conceptual knowledge in the formation of teachers' mathematical knowledge in problem-solving learning in elementary schools. Data collection through tests, questionnaires, and interviews. The test and questionnaire data were analyzed through linear regression statistical tests. Interview data were analyzed descriptively. Test the validity of interview data through triangulation of sources and theories. The results showed an effect of the level of mathematical disposition on mathematical knowledge (procedural and conceptual knowledge). Teachers with a high level of disposition have high procedural and conceptual knowledge. Meanwhile, teachers with low disposition level have lower procedural and conceptual knowledge. A positive mathematical disposition is a relationship between mathematical disposition procedural knowledge, and conceptual knowledge. It has implications for the formation of mathematical knowledge (procedural and conceptual knowledge) of a teacher in problem-solving learning. Also, the mathematical disposition is a prerequisite that supports the formation of mathematical knowledge (procedural and conceptual knowledge).